The STUDY OF MEDICINAL PLANTS USED BY TRADITIONAL HELEARS TO OVERCOME WOMAN PROBLEMS IN MASBANGUN VILLAGE, TELUK BATANG DISTRICT, KAYONG UTARA REGENCY - mariani, yeni; Rania, Rania; Yusro, Fathul; Wardenaar, Evy (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2019)
Pre and postnatal care, intensify breast milk, menstruation, vaginal discharge, body odor, women fertility, cosmetics, cervical cancer, and breast cancer are some of problems faced by women in the society. This study aims to analyze the used of medicinal plants by traditional healers in Masbangun village, North Kayong Regency that potentially could overcome these problems. The research was conducted with interviewing traditional healers who were selected by snowball sampling techniques. Interviews results obtained as much as 24 species of medicinal plants used in traditional medication to overcome women health problems and cosmetics. Zingiberaceae plants family, plants habitus herbs and trees (33.33% and 33.33%), plants roots and rhizomes (20.83% and 20.83%), with boiled processing method (45.83) and drunk administration method (66.67%) were the highest percentage mentioned by the traditional healers in this study to overcome woman health problems.